Desenvolvimento sustentável no Ceará: uma análise a partir da aplicação do barômetro da sustentabilidade - Silva, Andressa da (2017)
The measurement of the degree of territorial sustainability plays a key role in the diagnosis of existing human and environmental conditions. In the state of Ceará / BRA little has been done in order to evaluate in a specific way the sustainable development, so it was tried to determine through the Barometer of Sustainability the situation presented by the State and its 184 municipalities with regard to sustainable development. To this end, we selected a set of indicators and established Performance Scales that served as the basis for the construction of the Human Well-being and Environmental Well-being indices such indices together represent the level of sustainability of a territory. The results showed that no municipality in Ceará is sustainable, or potentially sustainable according to the Sustainability Barometer Scale classification, 59 municipalities presented intermediate level, while 122 municipalities are potentially unsustainable and three are unsustainable.